2010
DOI: 10.1080/10803548.2010.11076839
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Steam Formation and Migration in Firefighters’ Protective Clothing Using X-Ray Radiography

Abstract: X-ray radiography was used to quantify evaporation and moisture transfer in a multilayer firefighter protective clothing system with defined wetted layers exposed to low thermal radiation. Evaporation was faster and took place at higher temperatures if the moisture was located in the outer layers of the clothing system. Moisture that evaporated in the outer layers of the clothing system was found to move inwards and condense in the inner layers and on the cap of the measurement cell. Results found in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 8 publications
0
40
0
Order By: Relevance
“…In Table 4, a summary of the findings from previous research on thermal protective performance of fabrics under steam exposure is systematically presented. [92,93,95] fabric with a water vapor impermeable membrane provides better protection from steam than a fabric with a semi-permeable membrane. [47] and [46] Thickness and air permeability are the two most important property that can affect the thermal protective performance of fabrics under steam exposure.…”
Section: Thermal Protective Performance Under Steam Exposurementioning
confidence: 99%
“…In Table 4, a summary of the findings from previous research on thermal protective performance of fabrics under steam exposure is systematically presented. [92,93,95] fabric with a water vapor impermeable membrane provides better protection from steam than a fabric with a semi-permeable membrane. [47] and [46] Thickness and air permeability are the two most important property that can affect the thermal protective performance of fabrics under steam exposure.…”
Section: Thermal Protective Performance Under Steam Exposurementioning
confidence: 99%
“…These contradictory results, i.e. the moisture increases or decreases the protective performance of clothing can be attributed to the level of thermal radiation [4,8], the amount and location of the moisture [7,9,11], and the type of the fabric materials [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In practice, however, it is common to use correlation simply as a measure of strength and direction of a relationship, whether or not it is a cause-andeffect relationship. [21,22] reported that correlation's relationship are reported in many papers as a part of regression analysis but this in general is not how correlation should be applied for the simple reason that it measures different phenomena and between different types of variables than regression analysis [23]. The scale of the genetic parameters would show the amount of improvement by selection [24,25].…”
Section: Introductionmentioning
confidence: 99%